An expert system for the humidity and temperature control in HVAC systems using ANFIS and optimization with Fuzzy Modeling Approach - Soyguder, Servet; Alli, Hasan (Elsevier Science Sa, 2009)
The aim of this study is to design a HVAC system which damper gap rates have been controlled by PID controller. One of the dampers was controlled by using the required temperature for the interested indoor volume while the other damper was controlled by using the required humidity for the same indoor volume. The realized system has a zone with variable flow-rate by considering the ambient temperature and humidity. In the authors' previous theoretical work, PID parameters were theoretically obtained by using fuzzy sets for the same HVAC system. Optimization with Fuzzy Modeling Approach of PID parameters has been performed to maximize the performance of the system. The obtained PID parameters in the previous theoretical work were used in this study. Besides, the damper gap rates of a HVAC system with only one zone were predicted by using Artificial Neural Fuzzy Interface System (ANFIS) method. The input-output data sets of this system were first stored and then these data sets were used to obtain its intelligent model and control based on ANFIS. Efficiency of the developed ANFIS method was tested and a mean 99.98% recognition success was obtained. This paper shows that the values predicted with the ANFIS can be used to predict damper gap rate of HVAC system quite accurately. Therefore, faster and simpler solutions can be obtained based on ANFIS. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: ANFIS; Fuzzy Modeling Approach; Optimization; Damper gap-rate predicting; Air flow control; PID control; An expert HVAC system